'People in this country have had enough of experts': Brexit and the paradoxes of populism. Issue 1 (2nd January 2017) - Clarke, John; Newman, Janet
ABSTRACT: In June 2016, the United Kingdom voted to leave the European Union, creating massive political turmoil and controversy. Our aim in this paper is to contribute to a discussion about how to analyze such critical moments in policy and politics. Rather than searching for one 'real' cause (whether the micro-politics of the Conservative Party or popular disaffection from neo-liberalism), we offer a form of conjunctural analysis that highlights issues of multiplicity and heterogeneity. We sketch this approach and then explore two puzzles that have particular pertinence for Critical Policy Studies. One is the puzzle of populism: how new imaginings and representations of the 'British people' were constructed. The second is the puzzle of expertise; how antipathy to 'expert' knowledge was shaped to challenge British and European 'elites'. Conjunctural analysis, we argue, offers a vital means of engaging with such puzzles, and of grasping the heterogeneous and contradictory forces, tendencies, and pressures that enabled Brexit.